Identification and neuroprotective properties of NA‐184, a calpain‐2 inhibitor - Michel Baudry; Yubin Wang; Xiaoning Bi; Yun Lyna Luo; Zhijun Wang; Zeechan Kamal; Alexander Shirokov; Ed Sullivan; Dennis Lagasca; Hany Khalil; Gary Lee; Kathy Fosnaugh; et al. (Wiley, 2024)
Abstract Our laboratory has shown that calpain‐2 activation in the brain following acute injury is directly related to neuronal damage and the long‐term functional consequences of the injury, while calpain‐1 activation is generally neuroprotective and calpain‐1 deletion exacerbates neuronal injury. We have also shown that a relatively selective calpain‐2 inhibitor, referred to as C2I, enhanced long‐term potentiation and learning and memory, and provided neuroprotection in the controlled cortical impact (CCI) model of traumatic brain injury (TBI) in mice. Using molecular dynamic simulation and Site Identification by Ligand Competitive Saturation (SILCS) software, we generated about 130 analogs of C2I and tested them in a number of in vitro and in vivo assays. These led to the identification of two interesting compounds, NA‐112 and NA‐184. Further analyses indicated that NA‐184, (S)‐2‐(3‐benzylureido)‐N‐((R,S)‐1‐((3‐chloro‐2‐methoxybenzyl)amino)‐1,2‐dioxopentan‐3‐yl)‐4‐methylpentanamide, selectively and dose‐dependent inhibited calpain‐2 activity without evident inhibition of calpain‐1 at the tested concentrations in mouse brain tissues and human cell lines. Like NA‐112, NA‐184 inhibited TBI‐induced calpain‐2 activation and cell death in mice and rats, both male and females. Pharmacokinetic and pharmacodynamic analyses indicated that NA‐184 exhibited properties, including stability in plasma and liver and blood-brain barrier permeability, that make it a good clinical candidate for the treatment of TBI.